Association between depression symptoms and cognitive frailty in chronic kidney disease patients: a cross-sectional study - Zhang, Peng; Fan, Aiqing; Xie, Nian; Jiang, Jing; Peng, Shuzhi (Frontiers in Psychiatry, 2025)
ObjectiveCognitive frailty (CF) and depressive symptoms are prevalent in patients with chronic kidney disease (CKD) and may synergistically exacerbate adverse health outcomes. This study examined their association to inform early intervention strategies.MethodsDemographic and clinical data were collected from CKD patients across three hospitals in Shanghai. Depressive symptoms and CF status were assessed via standardized questionnaires. A logistic regression model and restricted cubic spline (RCS) analysis were employed to evaluate the association between depressive symptoms and CF.ResultsCF was diagnosed using the Frailty Phenotype (FP), Montreal Cognitive Assessment (MoCA), and Clinical Dementia Rating (CDR). Among 800 participants, 317 exhibited CF (prevalence: 39.6%). The adjusted logistic regression model revealed a significant positive association between Center for Epidemiologic Studies Depression (CES-D) scores and CF (OR=1.124, 95% CI: 1.094–1.156, p<0.001). RCS analysis demonstrated a nonlinear dose-response relationship: CF prevalence increased with rising CES-D scores until plateauing at a score of 9. The odds ratio (OR) exceeded the statistical significance threshold when CES-D scores reached 12. Subgroup analyses consistently supported this dose-response pattern.ConclusionDepressive symptoms are significantly associated with CF in CKD patients. Routine CES-D screening and provision of psychological support for patients scoring ≥12 may mitigate CF risk.